The evolutionary impact of childhood cancer on the human gene pool - Stoltze, Ulrik Kristoffer; Foss-Skiftesvik, Jon; Hansen, Thomas van Overeem; Rasmussen, Simon; Karczewski, Konrad J.; Wadt, Karin A. W.; Schmiegelow, Kjeld (Nature communications, 2024)
Germline pathogenic variants associated with increased childhood mortality must be subject to natural selection. Here, we analyze publicly available germline genetic metadata from 4,574 children with cancer [11 studies; 1,083 whole exome sequences (WES), 1,950 whole genome sequences (WGS), and 1,541 gene panel] and 141,456 adults [125,748 WES and 15,708 WGS]. We find that pediatric cancer predisposition syndrome (pCPS) genes [n = 85] are highly constrained, harboring only a quarter of the loss-of-function variants that would be expected. This strong indication of selective pressure on pCPS genes is found across multiple lines of germline genomics data from both pediatric and adult cohorts. For six genes [ ELP1 , GPR161 , VHL and SDHA / B / C ], a clear lack of mutational constraint calls the pediatric penetrance and/or severity of associated cancers into question. Conversely, out of 23 known pCPS genes associated with biallelic risk, two [9%, DIS3L2 and MSH2 ] show significant constraint, indicating that they may monoallelically increase childhood cancer risk. In summary, we show that population genetic data provide empirical evidence that heritable childhood cancer leads to natural selection powerful enough to have significantly impacted the present-day gene pool. Pathogenic germline variants associated with childhood cancer risk could be subject to evolutionary constraints. Here, the authors analyse publicly available germline data in large cohorts and observe that paediatric cancer predisposition syndrome genes are highly constrained in the general population.